Factors Affecting Tax Incentives of Energy Companies Listed on the Indonesia Stock Exchange - Tjia Siauw Jan (EconJournals, 2021)
This study aims to determine and explain the effect of company size, profitability, leverage, capital intensity, and inventory intensity on tax revenue for the tax amnesty program at energy companies listed on the Indonesia Stock Exchange. This research is a research that uses an associative approach. The sample in this study were 13 energy companies listed on the IDX in the 2013-2017 period which were determined by the Saturation Sampling method. This study uses descriptive statistics, multiple linear regression test for panel data models, hypothesis testing (t-test and F-test) and coefficient of determination as research analysis techniques. The results obtained show that partially the Capital Intensity, Leverage and Company Size affect tax revenue from the Tax Amnesty program, while Inventory Intensity and Profitability do not affect tax revenue from the Tax Amnesty program. Furthermore, Company Size, Inventory Intensity, Capital Intensity, Profitability and Leverage simultaneously affect tax revenue from the Tax Amnesty program. This means that tax revenue for the Tax Amnesty program at energy companies is influenced by company size, inventory intensity, capital intensity, profitability and leverage. Keywords: Company Size, Inventory Intensity, Capital Intensity, Profitability, Leverage, Tax Amnesty JEL Classifications: H23, H27 DOI: https://doi.org/10.32479/ijeep.11134